Novel porcine model of cutaneous myiasis: a training tool for healthcare workers. Issue 5 (13th February 2017) - Burns, Daniel S; Fletcher, D; Johnston, K; Bailey, MS; Campbell, K
Abstract : Cutaneous myiasis is a well-described problem in travellers to endemic regions including military personnel. Realistic training is important to ensure that healthcare workers have the confidence and expertise to recognise cutaneous myiasis and safely remove larvae if required. A model is described here that is simple, reproducible and realistic, and will allow for training of military healthcare workers in safe surgical removal of larvae when required.